Analisis Kasus Pelanggaran Hak Cipta Lagu “Helo Kuala Lumpur” Terhadap Lagu “Halo-Halo Bandung” Beserta Penyelesaian Sengketanya - Balqis Zhafirah Febriana (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
The advancement and development of technology and information will certainly have an impact on the creative industry, including music, which undoubtedly has a copyright. This copyright must be protected and enforced by appropriate laws considering the increasing risk of copyright infringement. For example, the copyright infringement case by the song "Helo Kuala Lumpur" against the song "Halo-Halo Bandung" clearly violates Article 40 Paragraph 1 and Article 7 Paragraph 3 of the Copyright Law. This is proven because the song has the same melody and rhythm, the lyrics have only been changed slightly, and the changes were made without the consent of the author and for commercial purposes. This infringement can be addressed through the Copyright Law and can be prosecuted through both civil and criminal proceedings with non-litigation or litigation methods. The Copyright Law is currently considered less effective, so it is necessary to improve the regulations and add provisions for preventive measures.